Jawabanmu

2014-02-13T00:06:52+07:00
f(x)=x^3 - 6x^2 + 9x - 2 = 0
ambil dari koef derajat tertinggi -> +-1
ambil dari suku tetap -> +-1, +-2
akar akar yang mungkin +-1/+-1 , +-2/+-1 -> 1,-1,2,-2
f(1) = (1)
³ - 6 (1)² + 9 (1) - 2
      = 1 - 6 + 9 -2 
      = 2 
≠ 0 (bukan akar dari pers)
f(-1) = (-1)³ - 6 (-1)² + 9 (-1) -2
      = -1 - 6 -9 -2 ≠ 0 (bukan akarnya)
f(2) = (2)³ -6 (2)² + 9 (2) -2
      = 8 -24 +18 -2
      = 26 - 26 = 0 (benar)
f(-2) = (-2)³ - 6 (-2)² +9 (-2) -2
       = -8 -24 -18 -2 ≠ 0 (bukan akarnya)

akarnya hanya 2